Pengaruh Model Problem Based Learning pada Pembelajaran Fisika Siswa SMA - Ovilia putri utami gumay (LPPM UNIVERSITAS PGRI SILAMPARI, 2022)
This research is motivated by the problems that the researchers obtained, namely the low learning outcomes of students' physics due to the lack of active involvement and independence of students in learning. The problem in this study is whether there is an effect of the Problem Based Learning model on physics learning for high school students. The purpose of this study was to determine the effect of the Problem Based Learning model on physics learning for high school students. This type of research is a real experimental research, the research design is in the form of control-group pretest-posttest. The population of this study was all students of class X SMA Negeri Purwodadi, Musi Rawas Regency for the 2018/2019 academic year, totaling three classes. The sample is class X.1 totaling 42 students and class X.3 students totaling 36 students. The data collection technique used is test. The data obtained were analyzed using t-test. Based on the results of the t-test analysis for the final test at the significance level = 0.05, it was obtained tcount > ttable (tcount = 2.65 > ttable = 1.67), so it can be concluded that there is an influence of the Problem Based Learning model on Physics learning for high school students.